“Sistema de indicadores de sostenibilidad ambiental para la conservación de áreas urbanas en el Cantón Arenillas” - Paredes Morán, Juan Gabriel (2023)
This research is based on the design of a system of environmental sustainability indicators for the conservation of urban areas in the Arenillas canton. The specific objectives were: carry out the current diagnosis of the urban area of the canton, establish environmental sustainability indicators for conservation and generate a conservation proposal for the urban areas of the Arenillas canton. The research was of a qualitative type whose methodology started from the review of general information to the particular one based on bibliographic information, in addition to carrying out on-site visits with the application of instruments such as the survey. We proceeded to make location maps with the help of Qgis for their respective spatial delimitation.